Intra- and inter-observer repeatability of radiographic measurements for previously slipped capital femoral epiphysis at skeletal maturity. (June 2013) - Lehmann, Trude G; Vetti, Nils; Laborie, Lene B; Engesæter, Ingvild Ø; Engesæter, Lars B; Rosendahl, Karen
Background: Recent studies suggest that even a mild slip of the femoral capital epiphysis may lead to later degenerative changes when undiagnosed. However, little is written on the accuracy of radiographic measurements used to diagnose a slip at skeletal maturity. Purpose: To assess the accuracy of radiographic measurements commonly used for assessment of previously slipped capital femoral epiphysis (SCFE) at skeletal maturity. Material and Methods: All children born at our hospital during 1989 ( n = 4006) were invited to participate in a follow-up hip trial at age 18–19 years. Erect pelvic anteroposterior and supine frog leg radiographs were obtained in a standardized fashion. For the purpose of this study, we selected a subset of 100 radiographs. To balance the data-set, we added another 28 radiographs from skeletal mature patients diagnosed and operated for a SCFE. Two observers independently measured Southwick's head-shaft angle, Murray's tilt-index, and the femoral head-neck angle. Intra- and inter-observer variation was assessed using the mean difference, with its 95% limits of agreement. Results: A high percentage of the images (40%), particularly for the measurement of the Southwick's head-shaft angle, were judged immeasurable by at least one observer. Mean head-shaft angle was 11.0° (SD = 17.0), head-neck angle was 8.0° (SD = 12.0), and Murray's tilt-index was 1.18 (SD = 0.4). For head-shaft angle, the mean difference between measurements (Observer 2) was 0.8° (SD = 2.7°, 95% limits of agreement –4.5° to 6.1°), while the corresponding figure for the Murray's tilt-index was 0.02 (SD = 0.08, 95% limits of agreement –0.18 to 0.14), and for the head-neck angle 0.9° (SD = 4.0, 95% limits of agreement of –6.9° to 8.7°). Slightly higher variance was seen for Observer 1 and between the two observers. Conclusion: Common radiographic measurements for the assessment of a previously slipped capital femoral epiphysis are relatively inaccurate in skeletal mature adolescents, in particular between observers (inter-observer), but also for the same observer (intra-observer). Our results underscore the importance of thorough standardization for both image and measurement technique when used in a clinical setting.